2021
DOI: 10.31234/osf.io/9ekpu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of attention control in complex real-world tasks

Abstract: Working memory capacity is an important psychological construct and many real-world phenomena are strongly associated with individual differences in working memory functioning. Although working memory and attention are intertwined, several studies have recently shown that individual differences in the general ability to control attention is more strongly predictive of human behavior than working memory capacity. In this review, we argue that researchers would therefore generally be better suited to studying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 420 publications
0
7
0
Order By: Relevance
“…Second, some researchers caution against using difference scores because they tend to show low reliabilities (Ackerman & Hambrick, 2020;Draheim et al, 2019Draheim et al, , 2022Hedge et al, 2018;Miller & Ulrich, 2013;von Bastian et al, 2020;Weigard et al, 2021). Von Bastian et al (2020 summarized the reliabilities of 406 measures of executive functions and found that the difference scores of inhibition tasks showed particularly low reliabilities with a mean reliability of .63 and a range from close to zero to close to one, whereas the reliability for shifting difference scores and updating scores were markedly higher (with mean reliabilities of .78).…”
Section: Difference Scores: High Validity or Further Psychometric Con...mentioning
confidence: 99%
“…Second, some researchers caution against using difference scores because they tend to show low reliabilities (Ackerman & Hambrick, 2020;Draheim et al, 2019Draheim et al, , 2022Hedge et al, 2018;Miller & Ulrich, 2013;von Bastian et al, 2020;Weigard et al, 2021). Von Bastian et al (2020 summarized the reliabilities of 406 measures of executive functions and found that the difference scores of inhibition tasks showed particularly low reliabilities with a mean reliability of .63 and a range from close to zero to close to one, whereas the reliability for shifting difference scores and updating scores were markedly higher (with mean reliabilities of .78).…”
Section: Difference Scores: High Validity or Further Psychometric Con...mentioning
confidence: 99%
“…Individual differences in the ability to control attention are correlated with a wide range of important outcomes, from cognitive task performance Conway et al, 2002;Draheim et al, 2021Draheim et al, , 2022Engle et al, 1999;Martin et al, 2020a;McVay & Kane, 2012) and academic achievement (Ahmed et al, 2019;Best et al, 2011) to health behaviors (Allan et al, 2016;Hall et al, 2008) and emotion regulation (Baumeister et al, 2007;Schmeichel & Demaree, 2010;Zelazo & Cunningham, 2007). As such, considerable time and effort has been invested in research on the nature of individual differences in attention control and their measurement (Lezak, 1982;McCabe et al, 2010;Willoughby et al, 2011;Zelazo et al, 2013).…”
mentioning
confidence: 99%
“…For example, ER choice has been replicated using unimodal stimuli (Feldman & Freitas, 2021;Shafir et al, 2018;Sheppes et al, 2011), but real-world stimuli are often multimodal and complex. This relative overabundance of information may negatively influence attentional control, which is one of the most robust predictors of realworld outcomes for cognitive behavior (Draheim et al, 2022). Other approaches have used realworld circumstances (Shafir et al, 2017), but individuals regulating emotion in their daily lives are also often untrained, stimuli are not previewed, and behavior is unprompted (Friedman & Gustavson, 2022).…”
Section: Introductionmentioning
confidence: 99%